2008
DOI: 10.1007/s10460-008-9134-0
|View full text |Cite
|
Sign up to set email alerts
|

Agronomist–farmer knowledge encounters: an analysis of knowledge exchange in the context of best management practices in England

Abstract: DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.The University of Gloucestershire makes no representation that the use of the materials will not infringe any patent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
165
0
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(185 citation statements)
references
References 40 publications
8
165
0
12
Order By: Relevance
“…When the issue is limited to the design of farming systems, the use of biophysical models in the form of a game in participatory workshops allows actors to explore a wide range of material resource use modes (Martin et al 2011). An important challenge for science is that these models need to consider the complexity and uncertainty associated with implementing biodiversity-based agriculture (Ingram 2008).…”
Section: Development Of Useful Scientific Artefactsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the issue is limited to the design of farming systems, the use of biophysical models in the form of a game in participatory workshops allows actors to explore a wide range of material resource use modes (Martin et al 2011). An important challenge for science is that these models need to consider the complexity and uncertainty associated with implementing biodiversity-based agriculture (Ingram 2008).…”
Section: Development Of Useful Scientific Artefactsmentioning
confidence: 99%
“…The first, in continuity with production-oriented agriculture, is based on increasing resource use efficiency (e.g. fertiliser, pesticides and water), recycling waste or byproducts of one subsystem in another (Kuisma et al 2013) and applying sound agricultural practices (Ingram 2008) or precision-agriculture technologies (Rains et al 2011). It is also based on replacing chemical inputs with organic inputs (Singh et al 2011) or genetically modified organisms (Godfray et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Farmers consistently rate face-to-face interactions as their preferred means of acquiring knowledge (Ingram, 2008), and prefer activities involving practical and hands-on means of teaching (Dodunski, 2014). In a study of advisor-farmer interactions, Ingram (2008) characterised different types of knowledge exchange events and concluded that facilitative encounters, where the advisor and farmer worked together to address the situation, sharing their knowledge and experience, were the most effective in providing farmer education and development. This suggests that advisors or veterinarians are an important source of knowledge for farmers to improve lamb or kid survival, but the nature of this exchange can have an impact on the uptake and use of the information.…”
Section: Knowledge Transfer: Challenges and Successesmentioning
confidence: 99%
“…This form of agriculture is implemented via best management practices (Ingram 2008), use of precision-agriculture technologies (Buman 2013) or improved plant cultivars (Vanloqueren and Baret 2009), or substitution (S) of chemical inputs by biological and environmentally less harmful ones (Singh et al 2011). Hereafter, we call it efficiency/substitutionbased agriculture.…”
Section: Introductionmentioning
confidence: 99%